2013
DOI: 10.1515/sg-2013-0004
|View full text |Cite
|
Sign up to set email alerts
|

Different diversity measures and genetic traits reveal different speciesgenetic diversity relationships: A case study in forest tree communities

Abstract: Relationships between species diversity and genetic diversity, the two most important elements of biodiversity, have recently attracted considerable interest in the field of community genetics. The present study contributes to this issue by addressing three questions that seem to have been ignored so far, namely whether the use of (a) different diversity measures, of (b) different components of diversity, and of (c) different genetic traits may lead to different assessements of speciesgenetic diversity relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Consequently, we might expect ‘pooled’ SGDCs to be more often positive than those centred on a single focal species. The empirical studies that pooled genetic data indeed found positive and significant multispecies SGDCs (Wehenkel et al , Robinson et al , Papadopoulou et al , Bergmann et al ) while invariably detecting non‐significant single‐species SGDCs. Decomposing these SGDCs should further reveal the environmental factors and/or the landscape features (e.g.…”
Section: Site and Community Factors Underpinning Sgdcsmentioning
confidence: 97%
“…Consequently, we might expect ‘pooled’ SGDCs to be more often positive than those centred on a single focal species. The empirical studies that pooled genetic data indeed found positive and significant multispecies SGDCs (Wehenkel et al , Robinson et al , Papadopoulou et al , Bergmann et al ) while invariably detecting non‐significant single‐species SGDCs. Decomposing these SGDCs should further reveal the environmental factors and/or the landscape features (e.g.…”
Section: Site and Community Factors Underpinning Sgdcsmentioning
confidence: 97%
“…p is the relative frequency of a variant i . Hill numbers can be used as explicit diversity measures at both species and genetic levels of diversity [2] [4] . Formally, …”
Section: Methodsmentioning
confidence: 99%
“…Species diversity and genetic diversity, the most basic elements of biodiversity, have long been treated as separate topics, although populations evolve within a community context [1] , [2] . Recent studies on community genetics and ecology have suggested that genetic diversity is not completely independent of species diversity [3] [4] [5] and may be correlated in three main ways: a) by a parallel process in which simultaneous responses of both levels of diversity to environmental factors may support a positive relationship [4] [6] ; b) species diversity may be causally controlled by genetic diversity within component species [7] ; and c) genetic diversity may be causally affected by the diversity and relative abundance of coexisting species if the species diversity of a community influences the selection system [8] with a negative association [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Let us start with a brief review on the species diversity (aka community diversity, biodiversity or ecological diversity) to explain the two essential elements of diversity concept in general, which should facilitate the introduction of our SNP diversity and similarity measures below. Species diversity refers to the ecological diversity of species in an ecological community, but diversity concept is equally applicable to genetic diversity (e.g., Nei 1973, Wehenkel et al 2006, Bergmann et al 2013 or other entities such as metagenome diversity (Ma & Li 2018). Conceptually, diversity possesses two essential elements: the variety and the variability of varieties (Gaston 1996;Chao et al 2014).…”
Section: Concepts and Definitionsmentioning
confidence: 99%